NOTES ON LEWIS-WILLIAMS AND DOWSON’S NEUROPSYCHOLOGICAL MODEL IN PREHISTORIC ART ANALYSIS - Daud Aris Tanudirjo (Humaniora, 2004)
Archeologists working on prehistoric art have considered neuro-psychological model in prehistoric art and analysis introduced by Lewis-Williams and Dowson a significant contribution in the efforts to find models in elucidating the meaning of prehistoric art. However, question and objections towards Lewis-Williams and Dowson ‘s neuropsychological model in prehistoric analysis show that the claim of its possible universal application needs further consideration. Ethnograhic data which so far has been used to strengthen the applicability of this model is also questionable. Thus, despite the fact the neuropsychological model in prehistoric art and analysis has provided another way of viewing, understanding and interpreting prehistoric art, it seems to have some weaknesses in terms of methodology and application.